Pediatric rectal perforation repaired via endoscopic clipping: An alternative technique - Mitchell H. Mirande; Madelyn R. Durhman; Forrest B. Bethel; Heather F. Smith; Raul A. Mirande (Elsevier, 2022)
Background: Pediatric rectal injuries are rare and occur mainly due to motor vehicle accidents, firearms, sexual abuse, and other varying causes of penetrating trauma. Common management of cases generally includes primary suture repair with or without diversion. Recent literature suggests that primary repair without fecal diversion may be performed safely in select children excluding presentation of shock, requirement of multiple blood transfusions, multiple other injuries, or extensive contamination; however, there is limited evidence to consider it yet a first-line strategy. Case presentation: A previously healthy 10-year-old boy was brought to the hospital emergency department following a traumatic rectal injury after falling on a rebar post. Flexible sigmoidoscopy with laparoscopic visualization demonstrated a 1-2 cm full-thickness laceration in the rectal mucosa 10 cm proximal to the anal margin. The laceration was successfully repaired with endoscopic clipping. Subsequently, the patient was discharged and had no additional complications during outpatient follow-up. Conclusions: This case demonstrates the successful use of endoscopic clipping as a treatment modality in the management of a grade IV pediatric rectal injury. While additional research is necessary, endoscopic clipping may serve as an additional treatment option when handling restrictive pediatric anatomy or as an alternative to primary suture closure with or without fecal diversion.